Implementation of Punishment of Student Discipline to Foster A Sense of Love For Memorization of The Qur'an - Indra Indra; M Nur Azis; Nunung Nurhayati; Nur Azizah; Rokhmatul Maula; Yuyun Yuliawati; Taufik Ridwan; Nur’ Ainil’ Azizah (Syntax Corporation, 2022)
Discipline is one of the attitudes that one needs to maintain in order to achieve a superior human resource. A punishment needs to be done considering that it is the right step to give a deterrent effect or resuscitate everything in order to get back on track. The importance of choosing punishment in order to have a good influence and has many benefits compared to just being a punishment instrument on someone. So, this research was conducted aimed at analyzing the discipline of students and the influence of punishment in the form of memorizing Qur'anic verses against love in the Qur'an. This research uses qualitative methods with field research types. Technical in the data analyzer in this study is the reduction of data presentation data and withdrawal of conclusions. The results showed that discipline becomes more increased because punishment in the form of qur'anic verses can also be used as a guideline for reminders of discipline. In addition, this punishment can also increase the love of the Qur'an. This study concludes that the punishment of memorization of the Qur'an for students who arrive late has differences with punishments in other schools. The reason why his punishment memorizes the Qur'an is because the Qur'an is the main guideline for a Muslim in pursuing his life path.